2020
DOI: 10.1016/j.fcr.2020.107788
|View full text |Cite
|
Sign up to set email alerts
|

The role of topography, soil, and remotely sensed vegetation condition towards predicting crop yield

Abstract: Foreknowledge of the spatiotemporal drivers of crop yield would provide a valuable source of information to optimize on-farm inputs and maximize profitability. In recent years, an abundance of spatial data providing information on soils, topography, and vegetation condition have become available from both proximal and remote sensing platforms. Given the wide range of data costs (between USD $0−50/ha), it is important to understand where often limited financial resources should be directed to optimize field pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…Since the irrigated fields received an additional water supply of 137.6 mm (US-Ne1) and 123.2 mm (US-Ne2), respectively from irrigation (see Table 1), the field variability may also reflect the underlying soil composition of the fields. Differences in nutrient amount and soil matrix structure have also been linked to crop yields at these sites 53 . On the other hand, the cumulative CubeSat E of the rainfed US-Ne3 site was higher than the cumulative precipitation amounts for the period August 19 until September 21 (35 days), which www.nature.com/scientificreports/ overlap with the sequence shown in the spatial maps of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the irrigated fields received an additional water supply of 137.6 mm (US-Ne1) and 123.2 mm (US-Ne2), respectively from irrigation (see Table 1), the field variability may also reflect the underlying soil composition of the fields. Differences in nutrient amount and soil matrix structure have also been linked to crop yields at these sites 53 . On the other hand, the cumulative CubeSat E of the rainfed US-Ne3 site was higher than the cumulative precipitation amounts for the period August 19 until September 21 (35 days), which www.nature.com/scientificreports/ overlap with the sequence shown in the spatial maps of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The triangular yellow markers mean RMSEs found that local scale models predicted yield more accurately than the region and state models. The variation of vegetation/climate conditions and other factors at different scales could be responsible for the discrepancies (Balaghi et al 2008;Franz et al 2020). Hence the improvement in yield estimation may be attributed to the finer grid level and the consideration of dynamic planting area, which provided more detailed and spatial representative data for yield estimation, especially in region A.…”
Section: Gridded Yield Estimation Resultsmentioning
confidence: 99%
“…RFR does not easily fall into overfitting and is more robust than other methods in terms of noise due to the introduction of randomness. Many studies have shown that the RFR method has good applicability in crop yield estimations (Breiman, 2001;Alberto et al, 2014;Franz et al, 2020).…”
Section: Rfr Methods For Estimating Winter Wheat Yieldmentioning
confidence: 99%